2012
DOI: 10.3168/jds.2011-4711
|View full text |Cite
|
Sign up to set email alerts
|

Manageable risk factors associated with the lactational incidence, elimination, and prevalence of Staphylococcus aureus intramammary infections in dairy cows

Abstract: Staphylococcus aureus intramammary infections (IMI) are a major cause of mastitis on farms worldwide. Incidence and elimination rates are the key determinants of prevalence of Staph. aureus, and risk factors associated with these rates must be identified, prioritized, and controlled to obtain long-term reduction in prevalence. The objectives of this study were to identify manageable risk factors associated with the lactational incidence, elimination, and prevalence of Staph. aureus IMI. A cohort of 90 Canadian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
81
0
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(95 citation statements)
references
References 34 publications
4
81
0
10
Order By: Relevance
“…This bacterium causes bovine mastitis and one of the most cost intensive diseases in the dairy industry (Dufour et al, 2012). In addition, enterotoxigenic S. aureus strain contains the potentially to make food borne intoxications in human transmitted by consuming the contaminated dairy products (Hennekinne et al, 2012;Jørgensen et al, 2005;Ostyn et al, 2010;Schmid et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This bacterium causes bovine mastitis and one of the most cost intensive diseases in the dairy industry (Dufour et al, 2012). In addition, enterotoxigenic S. aureus strain contains the potentially to make food borne intoxications in human transmitted by consuming the contaminated dairy products (Hennekinne et al, 2012;Jørgensen et al, 2005;Ostyn et al, 2010;Schmid et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…When gloves were worn, the odds ratio for new S aureus IMI incidence was 0.43 and the odds of eliminating existing infection was 2.2 times higher for herds where milkers wore gloves. 43 In a separate study, wearing gloves was also found to have a positive net economic benefit. 51 When friction is lost between the teat skin and the milking unit inflation, liner slips can occur, which allow air to be admitted in an uncontrolled fashion into the milking unit.…”
Section: Reducing Incidence Through Milking Practicesmentioning
confidence: 95%
“…A recent Canadian study found that it was also associated with a lower risk for prevalence and incidence of S aureus. 43 NMC annually publishes a list of approved premilking and postmilking teat disinfectant products. 44 For a premilking teat disinfection protocol to be most effective, it must have good coverage on the teat and be in contact with the teat skin for 30 seconds.…”
Section: Reducing Incidence Through Milking Practicesmentioning
confidence: 99%
“…The association between housing system and housing characteristics (bedding, stall base, stall length) and intramammary infection with Staphylococcus aureus differed for cows in different parities in the same herds. Similarly, the association of stocking density with elimination of infection depended on days in milk (Dufour et al, 2012). In Switzerland, lower herd SCC was described in organic farms with Alpine summer pasturing, while there was no effect of housing (except soft bedding) (Ivemeyer et al, 2009).…”
Section: Output: Milk Yield Per Cowmentioning
confidence: 96%